Development of multilayer systems Al/NAA/TiO2 with variable reflectance for optics applications (2018)
ABSTRACT: In this doctoral thesis, aluminum anodization was used to produce nanoporous anodic alumina (NAA) structures. The influence of the fabrication parameters on the NAA physical characteristics was determined. The effective medium approximation (E.M.A.) and Bruggeman’s equations were used to model and simulate the optical properties of the Al/NAA systems and as support to understand its optical behavior (reflectance and photoluminescence). Afterwards, the NAA samples were used to develop multilayer systems by means of titanium dioxide (TiO2) spray pyrolysis. The Al/NAA/TiO2 systems were also simulated and their optical properties were analyzed. As a starting point, as anodizing pretreatment aluminum electropolishing was carried out in three substrates and using the three different electrolytes described next. First, the aluminum alloy (AA) 8005 was electropolished using an acid electrolyte composed of sulfuric acid (H2SO4), phosphoric acid (H3PO4) and chromic acid (H2CrO) recording both current density and time. Second, a chromium free electrolyte was used to electropolish commercially pure AA 1100; this solution was composed by H2SO4, H3PO4 and nitric acid (HNO3). Third, the same alloy was electropolished in an alkaline electrolyte constituted by sodium phosphate (Na3PO4), aluminum sulfate (Al2(SO4)3) and sodium hydroxide (NaOH). Finally, the alkaline electrolyte was used as anodizing pretreatment of AA 1100 and pure aluminum (99.999%) surfaces. Afterwards, the materials and methods for fabricating NAA were presented. The previously electropolished AA 1100 was anodized at different potentials and during different times to establish the proper anodizing conditions to be used during the pure aluminum anodization. When the best anodizing conditions were found, 99.999% pure aluminum was used as a substrate to produce NAA samples with the two-step anodization process under mild anodization conditions in oxalic acid (H2C2O4). In consequence, the effect of the anodizing parameters such as applied potential, temperature and duration of the first step on NAA morphology and ordering is discussed. Samples with different thickness, pore diameter, interpore distance and ordering level were fabricated. Later, titanium dioxide (TiO2) layers were sprayed on top of the previously characterized NAA samples. The TiO2 layers were deposited by spray pyrolysis of a solution of titanium isopropoxide in anhydrous ethanol and sintered at 500°C. TiO2 thickness was modulated and the optical response measured. VI Finally, the optical properties of NAA are discussed in terms of photoluminescence (PL) and reflectance (R). The reflectance behavior of the Al/NAA and Al/NAA/TiO2 multilayer systems was analyzed with numerical simulations. The numerical simulations were based on the Transfer Matrix Method. The porosity of both the NAA film and the porous sprayed TiO2 film, was modeled using a Bruggeman effective medium approximation (E.M.A.). The results of this thesis are expected to highly contribute to the optical understanding of NAA and NAA/TiO2 in the UV-Vis zone in order to develop new nanodevices and optical applications.